ANALYSIS OF PERFORMANCE PARAMETER FROM BALANCED SCORECARD PERSPECTIVE IN INDONESIAN CONSTRUCTION FIRM - Siahaan, Antonius TP; Gunawan, Jessica; Juda, Ida (Academic Research Centre Services, 2015)
This research examines the relationships between variables in each balanced scorecard perspectives in Indonesian construction firm. Questionnaires were distributed through offline (sales intercept) and online (freeonlinesurveys.com) basis. We use Cronbach?s Alpha, Pearson Correlation, and Regressions to test the validity and relationship between variables in the model. From 162 questionnaires processed, the results show that there are positive correlation between hard & soft skills and SERVQUAL (tangibility, reliability, responsiveness, assurance, and empathy), SERVQUAL and customer perspectives, and customer perspective and sales. The firm should improve the non-financial perspectives to increase the sales (financial perspectives) since It is proven that there are significant effects between variables.